Edukasi Sosialisasi Mengenai Jenis,Bahaya, dan Dampak Penyalahgunaan Narkoba Pada Remaja di Desa Tengkudak - Kadek Adyatna Wedananta; arsita suradnyani (Jurnal Pengabdi, 2023)
The younger generation is said to be the backbone of the country and the future of the nation is said to be in the hands of the younger generation. The large number of adolescent populations resulted in the emergence of juvenile delinquency problems. Adolescence is a period of transition, which is a phase of development between childhood and adulthood. The main problem of adolescents in general is the search for identity. They have an identity crisis. This is a problem for every teenager. Therefore, they often have the urge to present themselves as a separate group. However, this encouragement often leads teenagers to serious problems, one of which is drug use. Drugs or narcotics is an abbreviation of Narcotics, Alcohol, Psychotropics and Addictive Substances. Narcotics are a group of psychoactive substances/drugs that are widely used and needed for healing efforts and health services as well as for the development of science. Today many cases of drug abuse are found, one group of people who are prone to being exposed to drug abuse are those in the age range of 15-35 years or the millennial generation. Because drug cases are always increasing every day, education or outreach about the dangers of drugs must always be carried out, especially among adolescents who are vulnerable to trying illegal drugs. In implementing the community service program, which is assisting the government by providing education to the younger generation with the theme "Socialization of Recognizing the Types, Dangers, and Impacts of Drug Abuse in Youth in Tengkudak Village" it is hoped that this will help educate the younger generation so they don't fall prey to drug abuse.  Keywords: Drugs, Education, abuse